2007
DOI: 10.5488/cmp.10.1.75
|View full text |Cite
|
Sign up to set email alerts
|

EPR and dielectric spectroscopy of reorienting Cr^{3+}-Li^{+} pair centres in Li_{2}Ge_{7}O_{15} crystal

Abstract: Earlier it has been shown that in the lithium heptagermanate Li 2 Ge 7 O 15 structure the chromium doping ions substitute the germanium hosts and create Cr 3+ -Li + pair centres. In the paper EPR and dielectric spectra of Li 2 Ge 7 O 15 :Cr 3+ crystal are studied in the temperature range 300 ÷ 500 K. The thermally activated reorientation of Cr 3+ -Li + pairs has been detected through EPR line width broadening and dielectric relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It may be assumed that pair centers can reorient due to thermal activation. Reorientation of the pair centers should be accompanied by: i) shortening of the configuration life time and ii) switching of defect dipole moments [35]. This is reflected in the typical temperature dependence of the imaginary part of dielectric permittivity of chromium doped LGO single crystals [35] along the a-axis of the crystal shown in fig.8.…”
Section: Study Of Fluorescence Spectra Of LI 2 Ge 7 O :Cr 3+ Crystalsmentioning
confidence: 97%
See 3 more Smart Citations
“…It may be assumed that pair centers can reorient due to thermal activation. Reorientation of the pair centers should be accompanied by: i) shortening of the configuration life time and ii) switching of defect dipole moments [35]. This is reflected in the typical temperature dependence of the imaginary part of dielectric permittivity of chromium doped LGO single crystals [35] along the a-axis of the crystal shown in fig.8.…”
Section: Study Of Fluorescence Spectra Of LI 2 Ge 7 O :Cr 3+ Crystalsmentioning
confidence: 97%
“…Reorientation of the pair centers should be accompanied by: i) shortening of the configuration life time and ii) switching of defect dipole moments [35]. This is reflected in the typical temperature dependence of the imaginary part of dielectric permittivity of chromium doped LGO single crystals [35] along the a-axis of the crystal shown in fig.8. Temperature dependence of Imaginary part ε''of permittivity ε=ε'-je'' of LGO:Cr 3+ , measured along crystal aaxis at the following frequencies : 0.5 kHz (1); 1 kHz (2); 5 kHz (3); 10 kHz (4).…”
Section: Study Of Fluorescence Spectra Of LI 2 Ge 7 O :Cr 3+ Crystalsmentioning
confidence: 97%
See 2 more Smart Citations
“…The models of Cr and Mn centers in Li 2 Ge 7 O 15 single crystal were proposed on the basis of EPR data ( [8][9][10][11] and the refs therein). It was shown that Cr ions produced excess to stoichiometry Li interstitials (A Li ) and formed Cr 3+ -Li + pair centers.…”
Section: Conductivity Of LI 2 Ge 7 O 15mentioning
confidence: 99%